Tourism Destination in Remote Area : Problems and Challenges of Tourism Development in North Halmahera as Remote and Border Areas of Indonesia-Philippines - Singgalen, Yerik Afrianto; Sasongko, Gatot; Wiloso, Pamerdi Giri (Graduate School, Universitas Brawijaya, 2018)
This paper will describe the problems and challenges in North Halmahera tourism development and describe the coordination, resources, disposition of executor and bureaucratic system in the process of tourism policy implementation by local government. This research used a qualitative method and case study approach. The method used in this research is qualitative with case study approach. This research conducted in Kakara Island, Tagalaya Island, Bobale Island, Kumo Island, Luari Beach, Paca Lake, Duma Lake, and Mamuya Hot Spring as the priority in North Halmahera Tourism Development Program by local government. The results of the evaluation indicate that the bureaucratic system, resources (human resources and sources of funding), the disposition of the commissioning and coordination was instrumental in the process of implementation of the policy on tourism. The implications of the implementation of tourism policy hampered are the lack of participation of the community and damage to facilities and access for tourism which threaten the sustainability of tourism. Thus, it can be noted that the challenges in the development of the leading tourist attraction in North Halmahera Regency are an effort to increase community participation through partnerships to achieve sustainable tourism.Keywords: Bureaucracy System, Coordination, Disposition, Resources, Tourism Policy